2019
DOI: 10.3389/fphys.2019.00872
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Responses of Skeletal Muscle to Acute Exercise in Diabetic Goto-Kakizaki Rats

Abstract: Physical activity exerts positive effects on glycemic control in type 2 diabetes (T2D), which is mediated in part by extensive metabolic and molecular remodeling of skeletal muscle in response to exercise, while many regulators of skeletal muscle remain unclear. In the present study, we investigated the effects of acute exercise on skeletal muscle transcriptomic responses in the Goto-Kakizaki (GK) rats which can spontaneously develop T2D. The transcriptomes of skeletal muscle from both 8-week-old GK and Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
10
0
2
Order By: Relevance
“…Some previous studies (Macia et al 2018, Morifuji et al 2012, Qi et al 2011 observed that running training did not reduce the increased blood glucose levels in diabetic GK rats. In contrast, other studies (Fu et al 2019, Kim et al 2011 showed that the high blood glucose levels in diabetic GK rats were decreased by running training. However, all these aforementioned studies (Fu et al 2019, Kim et al 2011, Macia et al 2018, Morifuji et al 2012, Qi et al 2011 used forced running training on a treadmill at a constant speed and time, and therefore, did not consider the effects of different running speeds and times.…”
Section: Voluntary Running Exercise and Diabetesmentioning
confidence: 72%
See 2 more Smart Citations
“…Some previous studies (Macia et al 2018, Morifuji et al 2012, Qi et al 2011 observed that running training did not reduce the increased blood glucose levels in diabetic GK rats. In contrast, other studies (Fu et al 2019, Kim et al 2011 showed that the high blood glucose levels in diabetic GK rats were decreased by running training. However, all these aforementioned studies (Fu et al 2019, Kim et al 2011, Macia et al 2018, Morifuji et al 2012, Qi et al 2011 used forced running training on a treadmill at a constant speed and time, and therefore, did not consider the effects of different running speeds and times.…”
Section: Voluntary Running Exercise and Diabetesmentioning
confidence: 72%
“…In contrast, other studies (Fu et al 2019, Kim et al 2011 showed that the high blood glucose levels in diabetic GK rats were decreased by running training. However, all these aforementioned studies (Fu et al 2019, Kim et al 2011, Macia et al 2018, Morifuji et al 2012, Qi et al 2011 used forced running training on a treadmill at a constant speed and time, and therefore, did not consider the effects of different running speeds and times. In this study, the growth-related increase in the fasting blood glucose levels of diabetic GK rats was inhibited by voluntary running exercise (Fig.…”
Section: Voluntary Running Exercise and Diabetesmentioning
confidence: 72%
See 1 more Smart Citation
“…Diabetes was shown to down-regulate the expression of TBC1D4 in skeletal muscle and adipose tissue of humans and rodents [ 11 , 12 , 13 , 14 ]. Tbc1d1 was shown to be up-regulated in diabetic rat muscle [ 15 ]. One study showed no significant change in both TBC1D1 and TBC1D4 protein abundance in diabetic patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that only a single session of exercise can attenuate hyperglycemia and enhance insulin sensitivity (Colberg et al, 2010). Over the decades, many studies on exercise have focused on peripheral tissues to explore the adaptive mechanisms in the T2D (Sylow et al, 2017; Hussey et al, 2011; Fu et al, 2019). Interestingly, recent research suggested that exercise training of obese mice could improve high-fat diet impaired proopiomelanocortin (POMC)-expressing neurons, protect against inflammation and aid in maintaining energy balance in the hypothalamus (Ropelle et al, 2010; Laing et al, 2016).…”
Section: Introductionmentioning
confidence: 99%